Proceedings of the 45th ACM Technical Symposium on Computer Science Education 2014
DOI: 10.1145/2538862.2538881
|View full text |Cite
|
Sign up to set email alerts
|

Camp CyberGirls

Abstract: In this paper we report on the design and results of a one-week, residential summer camp experience that introduced computing concepts to middle school girls in the context of an online, multiplayer, virtual world known as the Curiosity Grid. In contrast to programming environments designed specifically as teaching tools to introduce children to programming, virtual world programming exposes novice learners to a more representative computer science experience. Students write real code and get real syntax error… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(2 citation statements)
references
References 11 publications
0
1
0
Order By: Relevance
“…There have been considerable efforts to encourage girls to become interested in computer science (for a review of intervention strategies, see (Miliszewska & Moore, 2010)). Companies, governments, third-sector organisations and university academics have designed a variety of interventions 1 to promote computer science careers (Hunter & Boersen, 2017) and teach introductory CS concepts to girls, often in informal educational settings such as online programmes, summer camps or after school clubs (Hulsey et al, 2014;Thomas et al, 2017). While such programmes are designed with the best of intentions, the lack of diversity in CS and related STEM disciplines is a highly complex problem and interventions are often ineffective (MacDonald, 2014a).…”
Section: Introductionmentioning
confidence: 99%
“…There have been considerable efforts to encourage girls to become interested in computer science (for a review of intervention strategies, see (Miliszewska & Moore, 2010)). Companies, governments, third-sector organisations and university academics have designed a variety of interventions 1 to promote computer science careers (Hunter & Boersen, 2017) and teach introductory CS concepts to girls, often in informal educational settings such as online programmes, summer camps or after school clubs (Hulsey et al, 2014;Thomas et al, 2017). While such programmes are designed with the best of intentions, the lack of diversity in CS and related STEM disciplines is a highly complex problem and interventions are often ineffective (MacDonald, 2014a).…”
Section: Introductionmentioning
confidence: 99%
“…There have been many attempts at teaching computer programming through hands-on activities such as programming computer games [7] [8], robotics using widely available kits such as LEGO Mindstorms [9], and using mobile app development [10]. It was found that girls are able to learn using graphical programming softwares [11] [12] as well as line-based programming environments [13].…”
Section: Introductionmentioning
confidence: 99%